Inorganic / organic nano-composite plugging agent for shale drilling and preparation method of inorganic / organic nano-composite plugging agent
By introducing flexible polymer chain segments into rigid nanoparticles, inorganic/organic nanocomposite sealant is prepared, and the problems of unsatisfactory sealing effect and insufficient temperature resistance in the prior art are solved, and efficient sealing and high-temperature stability of mud shale formations are achieved.
Patent Information
- Application Number
- CN202311201478.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-18
AI Technical Summary
The existing drilling fluid sealing agent is difficult to effectively seal micro pores and microcracks in mud shale formations, and the temperature resistance and connection force are insufficient, resulting in unsatisfactory sealing effect.
By introducing flexible polymer chain segments containing association and other effects into rigid nanoparticles, the deformability of nanoparticles and the connection force with mud shale formations are improved, and inorganic/organic nanocomposite sealant is prepared to effectively seal the multi-scale micro pores and microcracks of mud shale formations.
The sealing agent is improved to seal the mud shale formation, enhance high temperature stability, and has a wide particle size distribution and physical and chemical synergistic sealing effect. It is suitable for drilling and leakage in mud shale formations.
Smart Images

Figure BDA0004454254500000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and specifically relates to an inorganic / organic nano-composite plugging agent for shale drilling and a preparation method thereof. Background Art
[0002] Statistics show that shale formations account for 70% of the total number of formations drilled, and more than 90% of drilling wellbore collapses occur in shale formations, of which hard and brittle shale formations with developed microcracks account for about two-thirds. Effectively preventing water from entering the formation and preventing the transmission of wellbore pressure to the formation is a prerequisite for stabilizing the wellbore. At present, the wall protection and collapse prevention technologies of water-based drilling fluids are mainly divided into physical plugging and chemical inhibition. The inhibition effect of drilling fluids alone cannot prevent collapse. The physical plugging effect of solid phase particles in drilling fluids must be used to isolate and prevent water from entering. The particle size of conventional drilling fluid plugging agents such as asphalt, paraffin and polyols cannot reach below the micron level, and the matching performance with the tiny pores and microcracks in shale formations is poor, making it difficult to achieve effective plugging. Nanoparticles used as drilling fluid plugging agents are mostly surface-modified products of nanoparticles such as nano-silicon dioxide and nano-magnesium oxide. The particle size distribution of this type of nano-plugging agent is relatively narrow, and it requires the composite use of multiple nanomaterials with different particle sizes. Moreover, most of them are rigid materials, which have weak connection with the formation and are easily detached due to interference from external factors, thus reducing the plugging effect.
[0003] Patent 109837073A discloses a shale plugging inhibitor for shale gas horizontal well drilling, which uses a new low molecular weight polymer AMPS / THAAB / MMA, oil and water mixed in proportion to achieve the purpose of simultaneously inhibiting shale hydration expansion and dispersion, thereby achieving a good shale plugging inhibition effect, but the inhibitor mainly plugs the micro-nano cracks of the formation through the emulsified oil phase, the plugging effect is limited, and the temperature resistance is poor. Patent CN109810678A discloses a shale formation plugging agent based on nanofiber composites for drilling fluid, which is prepared by compounding multiple types of nanoparticles. The plugging agent has little effect on the performance of the drilling fluid, has obvious shale plugging effect and high temperature and high pressure resistance; but the particle size distribution of the multiple nanoparticles it contains is mainly 10-50nm, the particle size range is narrow, and the plugging effect on the micro-nano cracks of the shale formation is limited. Patent CN113549432A discloses an environmentally friendly plugging agent for drilling fluid based on modified basalt fiber powder, which mainly comprises basalt fiber powder, nano-silica, surfactant, silane coupling agent, ethanol, polysaccharide polymer and other components. The plugging agent is mainly used as a plugging agent for drilling fluid while drilling and a plugging agent. It can improve its mechanical strength and compatibility with drilling fluid, as well as its chemical bonding strength with the formation and membrane efficiency, and is environmentally friendly; however, high temperature application conditions will reduce the plugging effect of the temporary plugging agent.
[0004] Therefore, further exploration of drilling fluid plugging agents for shale with characteristics such as wide particle size distribution and physical and chemical synergistic plugging effects has important research and application significance. Summary of the invention
[0005] The main purpose of the present invention is to provide an inorganic / organic nanocomposite plugging agent for shale drilling in view of the problems and shortcomings of the prior art. The present invention introduces flexible polymer chain segments containing association effects into rigid nanoparticles to improve the deformability of the nanoparticles and the connection between the nanoparticles and the shale formation, thereby improving the plugging ability of the plugging agent for multi-scale micropores and microcracks in the shale formation. The plugging agent has the characteristics of wide particle size distribution, physical and chemical synergistic plugging effect, good high-temperature stability, simple preparation method, and easy availability of raw materials. It is suitable for the fields of drilling leakage in shale formations.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] An inorganic / organic nano composite plugging agent, wherein the raw materials and their weight proportions include: 0.7-3.5 parts of modified nano particles, 10-50 parts of alkenyl amide monomers, 0.5-3 parts of alkenyl associative monomers, 20-50 parts of alkenyl sulfonic acid monomers, 10-20 parts of alkenyl cationic monomers, and 0.5-1.0 parts of initiators; the modified nano particles are formed by surface modification of the nano particles with a coupling agent.
[0008] In the above scheme, the surface modification step includes: adding a coupling agent alcohol solution to the alkaline nanoparticle alcohol dispersion, refluxing the reaction, and then purifying and drying.
[0009] In the above scheme, the preparation step of the alkaline nanoparticle alcohol dispersion includes: adding ethanol and nanoparticles into a reaction container in sequence, stirring evenly, adjusting the pH value to 7-8 with sodium hydroxide solution, and stirring at room temperature for 1.5-2h.
[0010] In the above scheme, the reflux reaction temperature is 60-85° C. and the time is 4-6 hours; a white emulsion is obtained.
[0011] In the above scheme, the purification step adopts a multiple dissolution-centrifugation process, wherein one or more of ethanol, acetone, etc. are used for dissolution; the drying temperature is 65-75° C., and the time is 12-24 hours.
[0012] In the above scheme, the mass ratio of the nanoparticles introduced into the alkaline nanoparticle alcohol dispersion to the coupling agent introduced into the coupling agent alcohol solution is 1:(0.1-0.5).
[0013] In the above solution, the nanoparticles can be selected from one of nano-silicon dioxide, nano-titanium dioxide and nano-silicon carbide.
[0014] In the above scheme, the particle size of the nanoparticles is 10 to 40 nm.
[0015] In the above scheme, the initiator can be ammonium persulfate or the like.
[0016] In the above scheme, the coupling agent can be selected from one of aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, vinyltriethoxysilane and the like.
[0017] In the above scheme, the vinylamide monomer is one or more of acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, vinylformamide, vinylacetamide and the like.
[0018] In the above scheme, the alkenyl sulfonic acid monomer is one or more of 2-acrylamide-2-methylpropanesulfonic acid, sodium methacrylic acid, and sulfonated styrene; the alkenyl associative monomer is one or more of N-hexadecyl acrylamide, N-octadecyl acrylamide, N-dodecyl acrylamide, hexadecyl dimethyl allyl ammonium chloride, and octadecyl dimethyl allyl ammonium chloride; the alkenyl cationic monomer is one or more of dimethyl diallyl ammonium chloride, allyl trimethyl ammonium chloride, and methacryloyloxyethyl trimethyl ammonium chloride.
[0019] The preparation method of the above-mentioned inorganic / organic nanocomposite plugging agent comprises the following steps:
[0020] 1) adding the modified nanoparticles into water, stirring at high speed and ultrasonicating to obtain a modified nanoparticle dispersion; adding alkenyl amide monomers, alkenyl sulfonic acid monomers, alkenyl associative monomers, and alkenyl cationic monomers into water, mixing them evenly, and mixing them with the modified nano solution, and adjusting the pH value of the mixed solution to 7-8;
[0021] 2) In an inert atmosphere, add an initiator and heat to carry out a free radical polymerization reaction to obtain a viscous solution;
[0022] 3) Purifying, drying and crushing the obtained reaction product to obtain the inorganic / organic nanocomposite plugging agent.
[0023] In the above scheme, the high-speed stirring rate is 2800-3000 r / min, and the time is more than 1 hour (preferably 1-2 hours); the ultrasonic power is 200-230 W, and the time is more than 1 hour (preferably 1-2 hours).
[0024] In the above scheme, the free radical polymerization reaction temperature is 50-80° C. and the time is 8-12 hours.
[0025] In the above solution, the particle size of the inorganic / organic nano-composite plugging agent is less than 200 meshes.
[0026] The principle of the present invention is:
[0027] The present invention firstly uses a coupling agent to perform surface modification on rigid nanoparticles and combines an optimized nanoparticle dispersion method, and then places the rigid nanoparticles in an alkenylamide-alkenylsulfonic acid-alkenyl association-alkenyl cation composite monomer system for reaction to prepare an inorganic / organic nanocomposite plugging agent: by introducing a flexible polymer chain segment containing an appropriate amount of high-temperature association, strong adsorption and the like into the rigid nanoparticle molecules, the deformability of the nanoparticles and the connection force with the mudstone formation are improved, thereby improving the plugging ability of the plugging agent for multi-scale micropores and microcracks in the mudstone formation and improving the high-temperature stability of the plugging layer; in addition, the introduced alkenylamide monomer structure can further ensure the effective residence of the plugging agent in the micro-voids, and the introduced sulfonic acid monomer can further improve the high-temperature stability of the obtained plugging agent, further ensuring the plugging effect of the obtained plugging agent under high temperature conditions.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1) The present invention introduces flexible polymer segments with high-temperature association and strong adsorption into rigid nanoparticle molecules to improve the deformability of the nanoparticles and their connection with the shale formation, thereby improving the plugging ability of the plugging agent on multi-scale micropores and microcracks in the shale formation, and effectively improving the high-temperature stability of the plugging layer;
[0030] 2) The nano plugging agent obtained by the present invention has a wide particle size distribution range and a strong connection with the mudstone formation, which can achieve a physical and chemical synergistic plugging effect on multi-scale micropores in the mudstone. At the same time, it has the characteristics of good high-temperature stability, simple preparation method, and easy availability of raw materials, and is suitable for promotion and application. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In the following examples, the nano-silicon dioxide, nano-titanium dioxide and nano-silicon carbide used are all provided by Aladdin, and their particle sizes are 15-30 nm, 10-25 nm and 20-40 nm respectively.
[0033] Example 1
[0034] An inorganic / organic nanocomposite plugging agent, the preparation method of which comprises the following steps:
[0035] 1) Disperse 20g of inorganic nano-silica in 300mL of ethanol, stir at 3000r / min for 120min, ultrasonically disperse for 120min, then add 2g of aminopropyltriethoxysilane, and use 20% sodium hydroxide reagent to adjust the pH of the solution to 7-8, reflux at 65°C for 4h, after which the sample after the reaction is dissolved in 300ml of ethanol, centrifuged in a centrifuge for 30min (4000r / min), take out the precipitate after centrifugation, dissolve it in 300ml of ethanol, repeat the centrifugation 4 times, take out the precipitate after the last centrifugation, put it in an oven at 65°C for 12h, and then use a pulverizer to crush it to obtain modified nanoparticles;
[0036] 2) 0.7 g of the modified nanoparticles were dispersed in 100 ml of deionized water, stirred at 3000 r / min for 1 h, and ultrasonicated for 1 h (220 W) to completely dissolve the modified nanoparticles in water to form a mixed solution, 10.2 g of acrylamide, 22 g of 2-acrylamide-2-methylpropanesulfonic acid, 1.8 g of N-dodecyl acrylamide, and 10.6 g of dimethyldiallylammonium chloride were weighed and added to the obtained mixed solution, and the pH of the mixed solution was adjusted to 7-8 with a sodium hydroxide solution with a mass concentration of 20%, then the temperature was raised to 65° C., and 10 mL of a 1 wt % ammonium persulfate aqueous solution was added dropwise, and the reaction was terminated after 8 h to obtain a white emulsion product;
[0037] 3) The obtained reaction product was repeatedly washed with acetone, placed in an oven at 70° C. for drying (12 h), and the dried product was crushed using a crusher (until it passed a 200-mesh sieve) to obtain the inorganic / organic nanocomposite plugging agent.
[0038] Example 2
[0039] An inorganic / organic nanocomposite plugging agent, the preparation method of which comprises the following steps:
[0040] 1) Disperse 20g of inorganic nano-titanium dioxide in 300mL of ethanol, disperse at high stirring (3000r / min) for 2h, and ultrasonically disperse for 2h (220W), then add 2g of vinyltriethoxysilane, and use 20% sodium hydroxide reagent to adjust the pH of the solution to 7-8, and reflux at 65°C for 4h. After the reaction, dissolve the sample in 300ml of ethanol, centrifuge it in a centrifuge for 30min (4000r / min), take out the precipitate after centrifugation, dissolve it in 300ml of ethanol, repeat the centrifugation 4 times, take out the precipitate after the last centrifugation, put it in an oven at 65°C for 12h, and then use a pulverizer to crush it to obtain modified nanoparticles;
[0041] 2) 1.4 g of the modified nanoparticles were dissolved in 100 ml of deionized water, stirred at 3000 r / min for 1 h, and ultrasonically dispersed for 1 h (220 W) to completely dissolve the modified nanoparticles in water to form a mixed solution, 10 g of vinylacetamide, 5 g of vinylformamide, 26 g of sulfonated styrene, 3 g of hexadecyldimethylallylammonium chloride, and 12 g of allyltrimethylammonium chloride were weighed and added to the mixed solution, and the pH of the mixed solution was adjusted to 7-8 with a 20% sodium hydroxide solution, then the temperature was raised to 65° C., and 10 mL of a 10 wt% ammonium persulfate aqueous solution was added dropwise, and the reaction was terminated after 8 h to obtain a white emulsion product;
[0042] 3) The obtained reaction product was repeatedly washed with acetone, placed in an oven at 70° C. for drying (12 h), and crushed (until it passes through a 200-mesh sieve) to obtain the inorganic / organic nanocomposite plugging agent.
[0043] Example 3
[0044] An inorganic / organic nanocomposite plugging agent, the preparation method of which comprises the following steps:
[0045] 1) Disperse 20g of inorganic nano-silicon carbide in 300mL of ethanol, stir at a high speed of 3000r / min for 2h, ultrasonically disperse for 2h (220W), then add 2g of 3-aminopropyltrimethoxysilane, reflux at 65°C for 4h, after which the sample after the reaction is dissolved in 300ml of ethanol, centrifuged in a centrifuge for 30min (4000r / min), take out the precipitate after centrifugation, dissolve it in 300ml of ethanol, repeat the centrifugation 4 times, take out the precipitate after the last centrifugation, put it in an oven at 65°C for 12h, and then use a pulverizer to crush it to obtain modified nanoparticles;
[0046] 2) 1.4 g of the modified nanoparticles were dispersed in 100 ml of deionized water, stirred at a speed of 3000 r / min for 1 h, and ultrasonicated for 1 h (220 W) to completely dissolve the modified nanoparticles in water to form a mixed solution, 4 g of N, N-dimethylacrylamide, 6 g of N, N-diethylacrylamide, 20 g of sodium methyl propylene sulfonate, 0.5 g of N-hexadecylacrylamide, 1.5 g of N-octadecylacrylamide, and 15 g of methacryloyloxyethyltrimethylammonium chloride were weighed and added to the mixed solution, and the pH of the mixed solution was adjusted to 7-8 with a sodium hydroxide solution with a mass concentration of 20%, then the temperature was raised to 65° C., and 5 mL of a 10% ammonium persulfate aqueous solution was added dropwise, and the reaction was terminated after 8 h to obtain a white emulsion product;
[0047] 3) The obtained reaction product was repeatedly washed with acetone, placed in an oven at 70° C. for drying (12 h), and crushed (until it passes through a 200-mesh sieve) to obtain the inorganic / organic nanocomposite plugging agent.
[0048] Comparative Example 1
[0049] An inorganic nano plugging agent, the preparation method of which comprises the following steps:
[0050] 1) 20 g of inorganic nano-silicon carbide was dispersed in 300 mL of ethanol, dispersed at a high stirring speed of 3000 r / min for 2 h, and ultrasonically dispersed for 2 h (220 W), and then 2 g of 3-aminopropyltrimethoxysilane was added, and refluxed at 65 ° C for 4 h to obtain a modified nano product sample;
[0051] 2) The sample after the reaction was dissolved in 300 ml of ethanol, and centrifuged in a centrifuge for 30 min (4000 r / min). The precipitate after centrifugation was taken out and dissolved in 300 ml of ethanol. The centrifugation was repeated 4 times. The precipitate after the last centrifugation was taken out and placed in an oven at 65°C for 12 h. Then, it was crushed using a pulverizer to obtain modified nanoparticles.
[0052] Comparative Example 2
[0053] An organic plugging agent, the preparation method of which comprises the following steps:
[0054] 1) Weigh 5 g of vinylacetamide, 5 g of vinylformamide, 20 g of sulfonated styrene, 3 g of hexadecyldimethylallyl ammonium chloride, and 10 g of allyltrimethylammonium chloride and add them to a mixed solution, adjust the pH of the mixed solution to 7-8 with a 20% sodium hydroxide solution, then heat the mixture to 65° C., and dropwise add 10 mL of a 1% ammonium persulfate aqueous solution, and terminate the reaction after 8 hours to obtain a viscous liquid product;
[0055] 2) The obtained reaction product is repeatedly washed with acetone, placed in an oven at 70° C. for drying (12 h), and crushed (to less than 200 meshes) to obtain the organic plugging agent.
[0056] Comparative Example 3
[0057] An inorganic / organic nanocomposite plugging agent, the preparation method of which comprises the following steps:
[0058] 1) Disperse 20g of inorganic nano-silica in 300mL of ethanol, stir at 3000r / min for 120min, ultrasonically disperse for 120min, then add 2g of aminopropyltriethoxysilane, and use 20% sodium hydroxide reagent to adjust the pH of the solution to 7-8, reflux at 65°C for 4h, after which the sample after the reaction is dissolved in 300ml of ethanol, centrifuged in a centrifuge for 30min (4000r / min), take out the precipitate after centrifugation, dissolve it in 300ml of ethanol, repeat the centrifugation 4 times, take out the precipitate after the last centrifugation, put it in an oven at 65°C for 12h, and then use a pulverizer to crush it to obtain modified nanoparticles;
[0059] 2) 0.7 g of the modified nanoparticles were dispersed in 100 ml of deionized water, stirred at a speed of 3000 r / min for 1 h, and ultrasonicated for 1 h (220 W) to completely dissolve the modified nanoparticles in water to form a mixed solution, 10.2 g of acrylamide, 22 g of 2-acrylamide-2-methylpropanesulfonic acid, and 1.8 g of N-dodecyl acrylamide were weighed and added to the mixed solution, and the pH of the mixed solution was adjusted to 7-8 with a 20% sodium hydroxide solution by mass, then the temperature was raised to 65° C., and 10 mL of a 1 wt% ammonium persulfate aqueous solution was added dropwise, and the reaction was terminated after 8 h to obtain a white emulsion product;
[0060] 3) The obtained reaction product was repeatedly washed with acetone, placed in an oven at 70° C. for drying (12 h), and the dried product was crushed using a crusher (to about 200 meshes) to obtain the inorganic / organic nanocomposite plugging agent.
[0061] Comparative Example 4
[0062] An inorganic / organic nanocomposite plugging agent, the preparation method of which comprises the following steps:
[0063] 1) Disperse 20g of inorganic nano-titanium dioxide in 300mL of ethanol, ultrasonically disperse for 120min (220W), then add 2g of vinyl triethoxysilane, and use 20% sodium hydroxide reagent to adjust the pH of the solution to 7-8, reflux at 65°C for 4h, after which the sample after the reaction is dissolved in 300ml of ethanol, centrifuged in a centrifuge for 30min (4000r / min), take out the precipitate after centrifugation, dissolve it in 300ml of ethanol, repeat the centrifugation 4 times, take out the precipitate after the last centrifugation, put it in an oven at 65°C for 12h, and then use a pulverizer to crush it to obtain modified nanoparticles;
[0064] 2) 1.4 g of the modified nanoparticles were dissolved in 100 ml of deionized water, and ultrasonically dispersed for 60 min to completely dissolve the modified nanoparticles in water to form a mixed solution, 10 g of vinylacetamide, 5 g of vinylformamide, 26 g of sulfonated styrene, 3 g of hexadecyldimethylallyl ammonium chloride, and 12 g of allyltrimethylammonium chloride were weighed and added to the mixed solution, and the pH of the mixed solution was adjusted to 7-8 with a 20% sodium hydroxide solution by mass, and then the temperature was raised to 65° C., and 10 mL of a 10 wt% ammonium persulfate aqueous solution was added dropwise, and the reaction was terminated after 8 h to obtain a white emulsion product;
[0065] 3) The obtained reaction product is repeatedly washed with acetone, placed in an oven at 70° C. for drying (12 h), and crushed (to about 200 meshes) to obtain the inorganic / organic nanocomposite plugging agent.
[0066] The plugging performance of the plugging agents prepared in the examples and comparative examples was tested below. The testing instrument used was a high-temperature and high-pressure sand disk plugging instrument, and the experimental temperature was 120°C.
[0067] Evaluation sample 1 is the inorganic / organic nanocomposite plugging agent prepared in Example 1;
[0068] Evaluation sample 2 is the inorganic / organic nanocomposite plugging agent prepared in Example 2;
[0069] Evaluation sample 3 is the inorganic / organic nanocomposite plugging agent prepared in Example 3;
[0070] Evaluation sample 4 is the plugging agent prepared in comparative example 1;
[0071] Evaluation sample 5 is the plugging agent prepared in comparative example 2.
[0072] Evaluation sample 6 is the plugging agent prepared in comparative example 3.
[0073] Evaluation sample 7 is the plugging agent prepared in comparative example 4.
[0074] Five kinds of drilling fluid test slurries were prepared with the above evaluation samples, and the specific steps were as follows: 16g of clay was added to seven high-stirring cups each filled with 400mL of tap water, and the mixture was cured at room temperature for 24h to serve as drilling fluid base slurries; 12g of evaluation sample 1, 12g of evaluation sample 2, 12g of evaluation sample 3, 12g of evaluation sample 4, 12g of evaluation sample 5, 12g of evaluation sample 6, and 12g of evaluation sample 7 were added to the seven drilling fluid base slurries, and the mixture was stirred at high speed to obtain seven kinds of test slurries; the seven kinds of test slurries were respectively placed in high-temperature aging tanks, hot-rolled at 120°C for 16h, and their plugging performances at 120°C within 1h were measured using a high-temperature and high-pressure sand disc plugging instrument.
[0075] First, the leakage of the test slurry is measured when the test pressure is 3.5Mpa and the test time is 0.5h, and then the test pressure is slowly increased and kept constant for 1h. If there is no sudden drop in the test pressure, the pressure bearing capacity of the plugging agent on the sand tray leakage layer at 120°C can be obtained. The test results are shown in Tables 1 and 2.
[0076] Table 1 The sealing effect of the composite plugging agent obtained in Examples 1-3 and Comparative Examples 1-4 on the sand tray leaking layer
[0077]
[0078] Table 2 Pressure bearing capacity of the composite plugging agent obtained in Examples 1-3 and Comparative Examples 1-4 on the sand tray leaking layer
[0079] Plugging agent Sand plate permeability (mD) 120℃ / 1h pressure bearing capacity (MPa) Example 1 50 8 Example 2 50 8 Example 3 50 8 Comparative Example 1 50 3.5 Comparative Example 2 50 4 Comparative Example 3 50 5.2 Comparative Example 4 50 5.5
[0080] It can be seen from the experimental data in Table 1 that the inorganic / organic nanocomposite plugging agent of the present invention has a relatively good plugging effect on sand trays with different permeabilities under a high temperature condition of 120°C.
[0081] It can be seen from the experimental data in Table 2 that the inorganic / organic nanocomposite plugging agent of the present invention can effectively plug the leakage layer of the sand tray. Under high temperature conditions of 120°C, its pressure bearing capacity can continuously reach 8MPa and can meet the long-term temperature resistance requirements.
[0082] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
Claims
1. An inorganic / organic nanocomposite plugging agent, characterized in that: The raw materials and their weight proportions include: 0.7-3.5 parts of modified nanoparticles, 10-50 parts of alkenyl amide monomers, 0.5-3 parts of alkenyl associative monomers, 20-50 parts of alkenyl sulfonic acid monomers, 10-20 parts of alkenyl cationic monomers, and 0.5-1.0 parts of initiators; the modified nanoparticles are formed by surface-modifying the nanoparticles with a coupling agent.
2. The inorganic / organic nanocomposite plugging agent according to claim 1, characterized in that: The coupling agent is one of aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and vinyltriethoxysilane.
3. The inorganic / organic nanocomposite plugging agent according to claim 1, characterized in that: The nanoparticles are one of nano silicon dioxide, nano titanium dioxide and nano silicon carbide.
4. The inorganic / organic nanocomposite plugging agent according to claim 1, characterized in that: The vinyl amide monomer is one or more of acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, vinyl formamide and vinyl acetamide.
5. The inorganic / organic nanocomposite plugging agent according to claim 1, characterized in that: The olefin sulfonic acid monomer is one or more of 2-acrylamide-2-methylpropane sulfonic acid, sodium methyl propene sulfonate, and sulfonated styrene.
6. The inorganic / organic nanocomposite plugging agent according to claim 1, characterized in that: The alkenyl associative monomer is one or more of N-hexadecyl acrylamide, N-octadecyl acrylamide, N-dodecyl acrylamide, hexadecyl dimethyl allyl ammonium chloride and octadecyl dimethyl allyl ammonium chloride.
7. The inorganic / organic nanocomposite plugging agent according to claim 1, characterized in that: The alkenyl cationic monomer is one or more of dimethyldiallyl ammonium chloride, allyltrimethylammonium chloride, and methacryloyloxyethyltrimethylammonium chloride.
8. The inorganic / organic nanocomposite plugging agent according to claim 1, characterized in that: The surface modification step comprises: adding a coupling agent alcohol solution into the alkaline nanoparticle alcohol dispersion, refluxing the mixture, and then purifying and drying the mixture.
9. The method for preparing the inorganic / organic nanocomposite plugging agent according to any one of claims 1 to 8, characterized in that: The steps include: 1) adding the modified nanoparticles into water, stirring at high speed and ultrasonicating to obtain a modified nanoparticle dispersion; adding alkenyl amide monomers, alkenyl sulfonic acid monomers, alkenyl associative monomers, and alkenyl cationic monomers into water, mixing them evenly, and mixing them with the modified nano solution, and adjusting the pH value of the mixed solution to 7-8; 2) In an inert atmosphere, add an initiator and heat to carry out a free radical polymerization reaction to obtain a viscous solution; 3) Purifying, drying and crushing the obtained reaction product to obtain the inorganic / organic nanocomposite plugging agent.
10. The preparation method according to claim 9, wherein the free radical polymerization reaction temperature is 50-80°C and the time is 8-12 hours.
Citation Information
Patent Citations
Nanofiber compound-based shale formation blocking agent for drilling fluid and preparation method
CN109810678A
Shale plugging inhibitor for drilling of shale gas horizontal well and preparation method thereof
CN109837073A
Environment-friendly plugging agent for drilling fluid based on modified basalt fiber powder, and preparation method thereof
CN113549432A
Organic / inorganic composite gel plugging agent with rigid interior and flexible exterior, and preparation method thereof
CN111218261A
High-temperature-resistant polymer microsphere nano-plugging agent for water-based drilling fluid, and preparation method thereof
CN111499790A
Cited By
Titanium-based quantum dot nano-composite high-performance water lock removing agent and preparation method thereof
CN120137633A
Temperature and pressure response type plugging empty capsule as well as preparation method and application thereof
CN121852015A